DISCOURSE OF COMMUNICATION PERSPECTIVE IN BEHAVIORAL ACCOUNTING ON BUDGET DESIGN IN A CORPORATION - MIS FERTYNO SITUMEANG (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2023)
This paper aims to discuss how behavioral accounting is becoming increasingly strategic in the budget planning of a corporation or organization. This study is a qualitative reflection with a literature study approach. Data is drawn from jurbal texts, books, electronic sources, digital sources, and other relevant source variants. The data are categorized into two main dimensions, namely communication behavior in budget design and communication in budget implementation. The results of the theoretical study show that the budget is one of the managerial tools used to plan, control and ensure the achievement of entity goals. However, it cannot be denied that the budget is a technical process that involves the role of individuals so that it allows for dysfunctional behavior that is born from the opportunistic attitude of the agent.